(3GdJhLg GdeSJbHdj dJaYjd egfI GdJObjb GdNGQLj hGdOGNdj aj GdEOGQGJ GdYehejIs - (3NdGUj(B, (3YeQs ((3GdLRGFQ s (3OGQ EjdjGA ddfTQ hGdJhRjYs, 2024)
(3BaGb JaYjd GdJObjb GdNGQLj h GdNGQLj aj GdGOGQGJ GdYehejI , eaghe GdJObjb GdeGdj GdeMGSHj , eaghe GdJObjb GdOGNdj h OQhg , eYGjjQ GdJObjb GdOhdjI , aYGdjI eMGaX GdMSGHGJ aj GdJUOjb Ydi GdMSGHGJ (B.s
Keywords: (3GdeYGjjQ GdeMGSHjIs; (3eQGLYI GdMSGHGJs